2006
DOI: 10.1007/s11663-006-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive kinetic model for the CO-CO2 reaction with iron oxide-containing slags

Abstract: A comprehensive kinetic model has been developed that enables the rate of the CO-CO 2 reaction with FeO x -containing slags to be predicted. The model was developed considering a reaction mechanism involving adsorption of CO 2 at the surface, charge transfer to the adsorbed CO 2 , and, finally, dissociation of . The rate-determining step of the reaction was found to be the formation of the ion, with the activation energy required to transfer charge to the CO 2 being dependent on slag composition. The model in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…48,58,59) It is inferred that slag penetration into the zirconia membrane and the phase transformation with an increase of the monoclinic phase amount can induce an increase of electronic conductivity of the zirconia membrane. Thus the external current (I ex ) is actually the sum of the pure oxygen ionic current ( I O 2−) and the internal electronic current (I e ) passing directly through the MSZ membrane as shown in Fig.…”
Section: (17′)mentioning
confidence: 99%
“…48,58,59) It is inferred that slag penetration into the zirconia membrane and the phase transformation with an increase of the monoclinic phase amount can induce an increase of electronic conductivity of the zirconia membrane. Thus the external current (I ex ) is actually the sum of the pure oxygen ionic current ( I O 2−) and the internal electronic current (I e ) passing directly through the MSZ membrane as shown in Fig.…”
Section: (17′)mentioning
confidence: 99%
“…20) To explain the relationship between rate constant and CO 2 /CO ratio, Grabke 1,2) proposed a theory of defect structure according to the electron transfer mechanism for the CO 2 reaction with iron oxide. However, it is difficult to accurately describe the interfacial kinetics because the defect structure of iron oxide such as wüstite and magnetite is much more complicated than assumed by Grabke. According to the usual understanding, CO 2 dissociation on the surface of metal and oxides containing iron oxide can be expressed as follows: If the electron can be considered as a chemical entity, 25) the rate of CO 2 dissociation will be expressed as Eq. (9) and the apparent rate constant will be given by Eq.…”
Section: The Relationship Of Chemical Reaction Rate Con-mentioning
confidence: 99%
“…The purpose of this article is to discuss the relationship, or lack thereof, between the electronic conductivity of iron oxide-containing slags and their catalytic behavior in reaction with gases. This work was originally undertaken as a gas-slag reaction study, [1,4] which, in common with previous work by the others, [5,6] indicated a mechanism involving free electrons at the surface of the slag (i.e., Reactions [3] and [4]). As a way to probe this mechanism further, the electronic conductivities of several slags were measured and reported.…”
Section: Mansoor Barati and Kenneth S Coleymentioning
confidence: 94%
“…A comprehensive model has recently been proposed by the authors [1] to present the reaction rate based on a multistep reaction mechanism as follows:…”
mentioning
confidence: 99%